PRÁTICA DE RALI NO PANTANAL SUL-MATO-GROSSENSE: PERCEPÇÕES SOCIOAMBIENTAIS E JURÍDICAS - JEFFERSON VILA MAIOR (2024)
This dissertation aims to alert and demonstrate the need for regulation by the public authorities of the State of Mato Grosso do Sul – MS, for the rally and off road practices that have been taking place in areas of the Pantanal and which are directly affecting the daily lives of communities and the local ecosystem. Public fiscal and extra-fiscal usage policies will also be addressed, which in short aim beyond compensation to the common good. Thus, this research will raise questions and provide an overview of the context of rally and off road practice in the Pantanal region of the state, as well as the need for the State to act in its regulatory role, adapting and disciplining the sustainable use of this important ecosystem. Brazilian for current and future generations. The methodological procedure will be historical, interpretative in nature with a dogmatic approach to investigate normative gaps and will also include documentary and bibliographical research. It is not intended to end discussions on the topic, but to contextualize perceptions in the face of a recently identified problem, and proposing possible solutions to public administration in favor of socio-environmental interests. Keywords: Pantanal. Public Power. Sustainability. Society.